(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
The article analyzes the macroeconomic conditions of the state; trends of growth of retail trade turnover in Ukraine and Volyn region are determined. The relationship between the level of household income and the volume of retail trade in the Volyn region In 2017, changes in the income of the population of Ukraine in% to the previous year are slower than in the Volyn region. Thus, if in 2017 the change in the income of the population of Ukraine compared to the previous 2016 was 129.3%, in the Volyn region - 130.4%. However, if in 2014-2015 the change in the volume of purchases of goods and services in% to the previous year in the Volyn region exceeded the pace in Ukraine as a whole, then since 2016 the opposite is happening: all-Ukrainian indicators are growing faster. Therefore, the above leads to the conclusion. that in the Volyn region there is a prospect for further development of retail trade, but these opportunities have not been fully used recently. A comparative analysis of the structure of cash expenditures of households in some countries and the Volyn region. If we compare with EU countries, then all comparable parameters there is a significant birth. Except for areas such as health care and consumer spending on alcohol and tobacco. (respectively Volyn region - 2.9%, EU countries - 3.9%, Ukraine - 3.1%) The main formats of the trade network of Volyn region are characterized; the level of specialization of the trade network of retail trade enterprises in Volyn and Ukraine is calculated. Identified areas in which retail trade in the Volyn region lags behind global trends: rather slow growth of non-cash payments; home delivery of products to the vast majority of retailers is not established; lack of shops without cash registers, etc.The regional factors of development of retail trade in the Volyn region are offered.